The Effect of Psychotria malayana Extract on Wound Healing in Male White Rats (Rattus Novergicus) Sprague Dawley Strain - Fairuz Fairuz; Khory Aurora Berty; Humaryanto Humaryanto (Jurnal Kedokteran Brawijaya, 2023)
Normal wounds are a complex and dynamic process, but they have a predictable pattern, and untreated open lesions are potentially infectious. According to the CDC (Centers for Disease Control), the incidence of surgical site infection (SSI) in the United States in 2018 was 157,500, with an estimated mortality rate of 8,205. Psychotria malayana plant contains flavonoids, alkaloids, and tannins, which play a role in the inflammatory phase and proliferation of wound healing. Many pharmacology effects of alkaloid and flavonoid activities include anti-inflammatory properties. The aim of this study was to determine the effect of Psychotria malayana extract ointment on wound healing in male white rats (Rattus norvegicus) of the Sprague-Dowley strain. This study is a laboratory experiment using the randomized post-test control only group design. Subjects were 25 male white rats (Rattus norvegicus) of the Sprague-Dowley strain. The rats were divided into five groups. The treatment was carried out for 14 days, and the wounds were shaved under anesthesia, and the skin was taken for histopathological evaluation after it had been examined macroscopically. An independent test showed that there is no significant difference macroscopically between control groups and treatment groups with a p-value >0.05. The Mann Whitney test showed a significant comparison microscopically at the level of angiogenesis, fibroblasts, and collagen in group negative control with group I (10% Psychotria malayana extract ointment) with a P value 0.05%. The conclusion is that 10% Psychotria malayana extract ointment increases fibroblast levels, angiogenesis, and collagen production in wound healing.